Remediation of Amitriptyline Pharmaceutical Wastewater by Heteroatom-Doped Graphene Oxide: Process Optimization and Packed-Bed Studies - Wan Ting Tee; Jasmine Chua; Jia En Yong; Billie Yan Zhang Hiew; Suyin Gan; Lai Yee Lee (Separations, 2023)
Amitriptyline residue released into the aquatic ecosystem can have detrimental consequences on marine organisms and human wellbeing via consumption of polluted water. With a uniquely large surface area and abundant functionalities, graphene oxide adsorption offers a remediation solution for such water pollution. This study focused on synthesizing a novel graphene-based adsorbent via ice-templating of boron-doped graphene substrate. The batch adsorption performance of the as-synthesized adsorbent was explored by central composite design (CCD), while its potential large-scale application was evaluated with a packed-bed column study. The CCD optimized conditions of 12.5 mg dosage, 32 min adsorption time, 30 °C operating temperature and 70 ppm concentration produced the highest removal efficiency of 87.72%. The results of the packed-bed study indicated that continuous adsorption of amitriptyline was best performed at a graphene bed of 3.5 cm in height, with 100 ppm of the pharmaceutical solution flowing at 2 mL/min. Furthermore, the breakthrough curve was effectively portrayed by the Log Bohart–Adams model. The as-synthesized adsorbent showed a high regeneration potential using ethanol eluent via multiple adsorption–desorption cycles. The results suggest the boron-doped graphene adsorbent in packed-bed as a highly effective system to remediate amitriptyline in an aqueous environment.